Severe exacerbation of psoriasis after cessation of methotrexate therapy successfully treated with cyclosporin A - Bartczyszyn-Kmiecik, Aleksandra; Żychowska, Magdalena; Reszke, Radomir; Reich, Adam (Dermatology Review/Przegląd Dermatologiczny, 2017)
Introduction . It is estimated that erythroderma affects about 1–2% of patients with psoriasis. Objective . To present a case of psoriatic erythroderma, which was effectively treated with cyclosporin A. Case report . A 31-year-old man was admitted to the department to treat erythroderma. Approximately 3 weeks prior to hospital admission he discontinued methotrexate treatment which, in addition with upper respiratory tract infection resulted in rapid recurrence of psoriatic lesions and development of erythroderma. Methotrexate 20 mg weekly was re-introduced to treat skin lesions. Despite such treatment, no satisfactory improvement was achieved. On the 13th day of hospitalization it was decided to start cyclosporin A (initially 200 mg/day, next increased to 300 mg/day). Cyclosporin A treatment was effective and well tolerated. Conclusions . Discontinuation of systemic treatment in patients with psoriasis may be associated with an exacerbation of the skin condition including erythroderma. Cyclosporin A is a valuable therapeutic option for patients with psoriatic erythroderma. The treatment is characterized by a rapid onset of action, good efficacy and generally favourable safety profile.